Correlation Between Parent’s Education Level and Frequency of Therapy with The Quality of Life in Children with Cerebral Palsy - Sylvia Evelyn Aritonang; Marietta Shanti Prananta; Marina A. Moeliono (Indonesian Journal of Physical Medicine & Rehabilitation, 2016)
Introduction : Cerebral Palsy (CP) is the most frequent cause of disability in children, CP has high risk to havelower quality of life (QoL) . There were several factors may have a relationship with quality of life (QoL) ofchildren with CP. The aim is to determine the correlation of QOL of patients with Cerebral Palsy.Methods : this study was a cross-sectional study, 60 subjects, children with CP aged 2–12 y.o divided into threegroups depend on age;2–4, 5–7, and 6–12 years old. The subjects’ QoL was measured using Pediatric ScaleQuality of Life (PedsQoL)Results: Study of 60 children with CP consisted 38 (63,3%) of male, were divided in three groups of age,respectively; 2-4 y.o; 12(20%), 5-7 y.o; 13 (21,7%), 8-12 y.o; 13(21,7%). Father’s and mother’s education levelwere primary school, junior, and senior high school respectively; 18(30%) and 18(30%), 9(15%) and 22(37%),33(55%) and 20 (33%). Frequency of therapy were less than 4 times/week was 31(51,7%), and 4 times/weekwas 29 (28,3%). There were a strong positive correlation between father’s and mother’s education level withPedsQoL; (r=0,67;p=0,00) and (r=0,70;p=0,00) , as well as between the frequency of therapy with PedsQoL;(r=0,69;p=0,00).Conclusion: Higher mother’s and father’s education level have correlation with higher PedsQoL,Keyword: cerebral palsy, pediatric quality of life, parent’s education level, frequency of therapy